KLASIFIKASI BENDA DALAM HUKUM PERDATA INDONESIA - Luthfi, Amir; Novi Maimory, Aminoel Akbar; Miswar, Miswar (Pahlawan Tuanku Tambusai University, 2025)
In the Indonesian civil law system, the regulation and classification of property hold a fundamental role in defining the rights and obligations of legal subjects in relation to legal objects. The classification encompasses tangible and intangible property, movable and immovable property, as well as consumable and non-consumable goods. This study seeks to systematically analyze the classification of property as stipulated in the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata or KUHPerdata), and to assess its relevance in contemporary legal and economic contexts. The research employs a normative juridical method, utilizing a statutory approach and legal literature review. Keywords : Civil Law, Property Classification, Indonesian Civil Code, Movable Property, Immovable Property